Hypertension in chronic kidney disease: What lies behind the scene - Ameer, Omar Z. (Frontiers in Pharmacology, 2022)
Hypertension is a frequent condition encountered during kidney disease development and a leading cause in its progression. Hallmark factors contributing to hypertension constitute a complexity of events that progress chronic kidney disease (CKD) into end-stage renal disease (ESRD). Multiple crosstalk mechanisms are involved in sustaining the inevitable high blood pressure (BP) state in CKD, and these play an important role in the pathogenesis of increased cardiovascular (CV) events associated with CKD. The present review discusses relevant contributory mechanisms underpinning the promotion of hypertension and their consequent eventuation to renal damage and CV disease. In particular, salt and volume expansion, sympathetic nervous system (SNS) hyperactivity, upregulated renin–angiotensin–aldosterone system (RAAS), oxidative stress, vascular remodeling, endothelial dysfunction, and a range of mediators and signaling molecules (e.g., various autocoids, hormones and factors, ion channels, reactive oxygen species and enzymes), which are thought to play a role in this concert of events, were emphasized. As the control of high BP via conventional or non-conventional, yet relatively new, therapeutic interventions can represent the key strategy to reduce not only elevated BP but also the CV burden in kidney disease, evidence for major strategic pathways that can alleviate the progression of hypertensive kidney disease was highlighted. In this regard, examples focusing on the impact of RAAS antagonists, renal nerve denervation, baroreflex stimulation, and other modalities affecting BP were put forward to provide interesting perspectives on the management of hypertensive nephropathy and the associated CV comorbidities.